Етнокультурний контекст художніх творів Марії Матіос "Солодка Даруся", "Ніколи не навпаки" - Звягіна, Ганна Олександрівна; Zviahina, H. O. (My University, 2019)
У цій статті ми аналізуємо українську етнічну культуру в контексті романів Марії Матіос «Солодка Даруся», «Ніколи не навпаки». Мета статті – обговорення відображення української етнічної культури у творчості письменниці. Ми розглядаємо раціонально-пізнавальний аспект етнічної ідентифікації усвідомлення себе як члена етнічної спільності з притаманними їй властивостями та якостями, які повторюються в людях відповідної групи. Акцентуємо увагу на важливості ролі самоідентифікації, оригінальності моделі світу письменниці, концептуальною домінантою якої є нація і Буковина. In this article, we analyze Ukrainian ethnic culture through the context of novels of Maria Matios «Solodka Darusia», «Nikoly ne navpaky». The theoretical frameworks based on anthropological linguistics and linguistic anthropology. They explores the language function as one of the cultural subsystems. The purpose of the article is to discuss a reflection of Ukrainian ethnic culture in the writer’s work. We consider the rational-cognitive aspect of ethnic identity, ethnic self-awareness, ethnicity that is considered to be shared characteristics such as culture, language, religion, and traditions, which contribute to a person or group’s identity and regarded by others as a distinct community by virtue of certain characteristics that will help to distinguish the group from the surrounding community. We emphasis on originality of the model of the writer’s world. Conceptual dominant of this world is the nation and Bukovina.
Etnocultural context of novels of Maria Matios «Solodka Darusia», «Nikoly ne navpaky»
Keywords: етнічний контекст; етнічна культура; етнічні стереотипи; національна ідентичність; еthnocultural context; ethnic culture; ethnic stereotypes; national identity